A Multi-Agent Game-Based Incremental Distribution Network Source–Load–Storage Collaborative Planning Method Considering Uncertainties - Yang, Nan; He, Ye; Dong, BangTian; Qin, Tao; Ding, Li; Yang, XingLei; Yao, JunWei; Huang, YueHua; Wang, ShuoHao; Zhang, Lei; Zhu, BinXin; Xiong, Wei; et al. (Frontiers in Energy Research, 2022)
How to obtain the optimal decision-making scheme based on the investment behavior of various stakeholders is an important issue that needs to be solved urgently in incremental distribution network planning. To this end, this paper introduces the virtual player “Nature” to realize the combination of game theory and robust optimization, and proposes an incremental distribution network source-load-storage collaborate planning method with multi-agent game. Firstly, the planning and decision-making models of DG investment operator, distribution network (DN) company, power consumers and distributed energy storage (DES) investment operator are constructed respectively. Then, the static game behaviors between DG investment operator and distribution network company, as well as DG investment operator and DES investment operator are analyzed based on the transfer relations between these four participants. At the same time, robust optimization is used to deal with the uncertainty of DG output, and the virtual player “Nature” is introduced to study the dynamic game behavior between the DG investment operator and the distribution company. Finally, a dynamic-static joint game planning model is proposed. The simulation results verify the correctness and effectiveness of the proposed method.